Weberian model of bureaucracy: The best fit/misfit for development administration - Balaram, Anuradha (2000)
Examining relevance of Weberian `ideal' bureaucratic system for developing countries, the author analyses functioning of the rational-legal model of bureaucracies in developing countries, to identify points of departure from the Weberian `ideal' to stress that it is neither appropriate for attaining developmental goals nor acceptable to the prevailing socio-cultural and political environment of developing countries due to its severe criticism in the developed world. Opposing its application in developing countries, she concludes that each development administration organisation should have its own model through alignment of Information Technology into the organisational strategy. - Reproduced
Keywords: Weber, Max; Development administration; Bureaucracy